Understanding the Correlation Between Remote Working and Flow Experience: Analysing Job Satisfaction, Turnover Rate and Employee Engagement in Remote Conditions - Monica Kunte; Daksh Kumar Singh; Jatin Meshram; Nischal Chhettri (Australasian Accounting, Business and Finance Journal, 2025)
This research paper explores the link between employee engagement, job performance, and the flow experience in remote work settings, offering fresh insights for organisations. Findings reveal that fostering employee engagement significantly enhances job performance, independent of variables like job satisfaction and tenure. The study findings suggest that tailored engagement strategies are proven to be crucial, particularly in creative job roles. The study also advocates that autonomy and positive workplace relationships are vital for efficiency and well-being. The study strongly reflects on the COVID-19 impact, highlighting both challenges and opportunities in remote work. Ultimately, it underscores the pivotal role of employee engagement in organisational success and employee welfare in new-age workplaces.
Keywords: Remote work; Flow experience; Job satisfaction; Turnover rate; Employee engagement